MENJAGA KESATUAN DALAM PERBEDAAN: STUDI ATAS HADIS 73 GOLONGAN DAN IMPLIKASINYA DALAM KEHIDUPAN KONTEMPORER - Ali Yusuf Muzakki; M. Farid Zaini (Jurnal Shaf, 2026)
This study explores the fiqh-based interpretation of the well-known hadith concerning the division of the Muslim ummah into 73 sects, in which only one is deemed "saved." Rather than viewing this hadith as a justification for sectarianism and exclusion, this research approaches it through the lens of classical and contemporary Islamic jurisprudence to emphasize tolerance, unity, and the ethical management of religious differences. The analysis draws from diverse sources within Sunni scholarship to understand the historical and theological context of the hadith and its misinterpretation by radical or exclusivist groups. This paper argues that the "saved group" (al-firqat al-nājiyah) should not be monopolized by any particular sect or school of thought, but rather should be understood as those committed to the core Islamic principles of tawhid, justice, and mercy. Furthermore, the study highlights the relevance of fiqh in addressing challenges of pluralism, political fragmentation, and intra-Muslim intolerance in modern societies. By promoting values such as ukhuwah Islamiyyah (Islamic brotherhood), tasamuh (tolerance), and ijma’ (scholarly consensus), this research suggests that Islamic law offers strong foundations for fostering cohesion in the Muslim world. The findings urge contemporary Muslims to embrace differences as a source of strength, not division, and to actively contribute to unity without erasing diversity.